International Perspectives on Physician Assistance in Dying - Orentlicher, David (The Hastings Center report, 2016)
When the Supreme Court of Canada recognized a constitutional right to “medical assistance in dying” last year—and the nation's Parliament enacted legislation to implement the right earlier this year—Canadian lawmakers could look to two different models for guidance. The Netherlands and Belgium recognize a broad right to assistance in dying, while Oregon and elsewhere in the United States have a narrow right. In some ways, assistance in dying in Canada follows the Dutch-Belgian approach, while, in other ways, it seems more American. Two societal factors seem relevant to the different approaches: the role that religion plays in people's lives and the trust that people place in their governments and health care systems. As other governments consider legalizing assistance in dying, an important question is whether some restrictions on the right are particularly critical. The experience to date suggests that requiring patients to be terminally ill has provided the best protection against misuse.